The experience of nurses in providing holistic nursing care for COVID-19 patients at Banyuwangi Hospital - Pramesti Wilujeng, Atik; Yanuar Fahmi Pamunhgkas, Akhmad; Rizal Mahardika, Dwiky; Sonontiko, Essy (Universitas Airlangga, 2023)
Background: COVID-19 is a new virus that was discovered at the end of December 2019 and has marked a global pandemic around the world. Not only has a high-risk infection, nuthe most contact with COVID-19 patients are also at risk of experiencing physical and emotional stress. Anxiety, nurses' fear about the risk of contracting the COVID-19 virus can lead to unprofessional attitudes and behavior of nurses in providing holistic nursing care to the patients. This study aimed to explore the experience of nurses in providing holistic nursing care to COVID-19 patients Methods: This research used phenomenological qualitative research. Data collection was done by in-depth interview. The participants in this study were 7 nurses who served in the isolation room of Blambangan Hospital, Banyuwangi. Purposive sampling method was used to select participants according to the inclusion criteria. Descriptions of nurses experiences were analyzed using the Colaizzi approach. Results: The study result revealed 6 themes; changes in the emotional status of nurses while caring for COVID-19, social stigma against COVID-19 nurses, support during caring for COVID-19 patients, expectations during caring for COVID-19 challenges during caring for COVID-19 patientsand fulfillment holistic nursing carefor COVID-19 patients. Conclusion: The nurses experience in treating COVID-19 patients showed that when they ware caring for patients, they have to go through ups and downs. This research was expected to improve nursing services, prepare nurses to adapt to the growing pandemic, and as a reference for further research related to the experience of nurses in treating COVID-19 patients.